The Impact of Chair-CEO Duality on R and D Investment in ‎Firms Led by Highly Educated CEOs - Al-Dubai, Shehabaddin Abdullah Abdulwadod (International Journal of Accounting and Economics Studies, 2025)
This study investigates the impact of Chair–CEO duality on R and D investment intensity in firms managed by highly educated CEOs using a ‎dataset of 877 firm-year observations from companies listed on the Shanghai and Shenzhen Stock Exchanges between 2015 and 2020. Employing Hausman–Taylor estimations to address potential endogeneity, the results reveal that Chair–CEO duality has a significantly positive ‎effect on R and D investment in such firms. In the context of highly educated CEOs, the concentration of authority does not appear to lead to ‎self-serving or inefficient behaviors but rather to more purposeful investments in innovation. Moreover, the results highlight the differences ‎in how CEOs approach R and D decisions based on the type of postgraduate degree they hold. These findings offer important insights into ‎how leadership education and governance structures jointly influence firms’ strategic-innovation outcomes‎.
Keywords: Corporate Governance; Research and Development Investment R&D; Chair-CEO Duality; Higher Education; China